Environmental Pollution in the Perspective of Civil Law - Fauzi, Ahmad Nur; Iskandar, Hardian (LEGAL BRIEF, 2024)
: Issues relating to the environment are intrinsically linked to human behavior, as there is a significant relationship between humans and their environment, characterized by the idea that humans have a right to the environment. Environmental issues are important challenges that require our collective attention, as they are closely linked to safety, public health, and the functioning of our daily lives. The objective of the issue at hand is for the Government to take the initiative to foster public awareness and ensure effective implementation of environmental laws and regulations. This is important to prevent any prejudice against environmental management policies enforced by public enterprises. Therefore, law enforcement related to environmental pollution is very important. The approach method implemented in this research is normative research. The findings of this research show that to address environmental pollution, effective solutions are needed that aim to facilitate environmental restoration, as outlined in the Environmental Law No. 32 of 2009. This law manages environmental law to also include measures designed to prevent actions that may cause environmental degradation, thereby contributing to the mitigation of such damage. In addition, this law also emphasizes the need for environmental law enforcement within the framework of Civil Law